Us and others : social identities across languages, discourses and cultures - Duszak, Anna. (Amsterdam ; Philadelphia : John Benjamins Pub., 2002)
It is natural for people to make the distinction between in-group (Us) and out-group members (Others). What is it that brings people together, or keeps them apart? Ethnicity, nationality, professional expertise or life style? And, above all, what is the role of language in communicating solidarity and detachment?The papers in this volume look at the various cognitive, social, and linguistic aspects of how social identities are constructed, foregrounded and redefined in interaction. Concepts and methodologies are taken from studies in language variation and change, multilingualism, conversation.
Us and Others; Editorial page; Title page; LCC data; Contents; Us and Others: An introduction; Part I: Discourses in space; Grammar and function of we; Between us and them in Chinese; Viewpoint and in/out-group membership for Japanese; The space in identity; Constructing identities in language learning MOOs; Part II: Discourses in polyphony; Ethnolects as in-group varieties; The construction of identity and group boundaries in Catalan Spanish; Code-switching, code-crossing, and identity construction in a society in transition, South Africa; Part III: Discourses of transition.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Group identity; Group identity -- Cross-cultural studies; Sociolinguistics; Language and culture; Social Identification; Identité collective; Identité collective -- Études transculturelles; Sociolinguistique; Langage et culture; group identity; sociolinguistics; PSYCHOLOGY -- Social Psychology; Group identity; Language and culture; Sociolinguistics; Sociale identiteit; Cross-cultural studies